Strategic Directions of Tourism Industry Development in the Digital Economy - I. Z. Chkhotua (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2021)
Tourism and the hospitality industry is a strategically important sector of the economy with a significant multiplier effect, performing a number of important functions to ensure the inte- grated development of the territory. The strategic priorities for the development of the industry should be implemented in the formalized document of the Strategy that brings tourism to a new stage of development, focusing all the state’s resources on achieving Russia’s strategic goals in this tourism industry. The significant natural, recreational, cultural potential of our country is an indisputable competitive advantage in determining and approving the strategic directions of tourism development.The purpose of the article is to propose strategic vectors for transforming the tourism in- dustry, determined in response to the crisis in the economy and the global trend of digitalization: restructuring the business model, changing the product strategy towards technology, building a new marketing strategy with the help of modern ICT, changing the requirements for the tourism industry personnel, development of a new communication strategy in response to the changing behavior of the tourist himself. Comprehensive development of the tourism industry is possible only with a strategic transformation of all these areas.